Interfacial shear strength studies of experimental carbon fibres, novel thermosetting polyurethane and epoxy matrices and bespoke sizing agents. (14th September 2016) - Gnädinger, Florian; Middendorf, Peter; Fox, Bronwyn
Abstract: The strength and nature of the fibre-matrix connection affects many of the key mechanical characteristics of composite parts. The complex interplay of fibre surface, sizing agent and matrix material has been a longstanding problem and receives substantial attention when new ingredients are introduced. For the first time, this study investigated a novel thermosetting polyurethane resin together with a set of experimental carbon fibres. The fibres were manufactured using a unique facility that closely models a commercial production line. This equipment allowed extracting fibres after carbonisation, after electrochemical surface treatment and after coating with epoxy, polyurethane and polyamide based sizing agents. A commercial carbon fibre and a state of the art epoxy resin were selected as reference materials. The single fibre fragmentation test was used to measure the interfacial shear strength (IFSS) of the resulting combinations. The results show the enormous importance of etching away the relatively inert outer layer during surface treatment as the IFSS increased by factor 2.6. The newly developed polyurethane resin showed for unsized fibres up to 50% higher values for the IFSS than corresponding combinations employing epoxy resin. This superiority melted down to 5–21% when looking at the sized fibres, showing the need for developing sizing agents that facilitate adhesion to polyurethane matrices. A relative advantage of identical sizing and matrix polymer could be found when looking at sized fibres. Photoelastic investigations of the fragmented specimens supported the measured values for the IFSS. There was a close correlation between high IFSS results and strong photoelastic stress patterns.